Factors Influence Green Practice Adoption in Johor Manufacturing Industry - Chui-Ling, Haw; Mohd Nor, Norasmiha (Research in Management of Technology and Business, 2020)
This study examines four factors that may influence green practice adoption. The determinant factors are organizational support, quality of human resource, customer pressure and governmental pressure. Questionnaires were distributed to ISO 14001 certified firms in Johor manufacturing industry, and only 38 questionnaires were returned. The results show all factors didn’t influence green practices adoption. Due to the small sample size, generalizations could not be made. Limitation of this can be used as a suggestion for further research. The future study also should examine another influential factor such as environment uncertainty and technological complexity. Moreover, by increasing the sample size, more validated analyses may be performed in the future.